Women's reproductive health and features of eating behavior - S. I. Yelgina; I. S. Zakharov; E. V. Rudaeva (Фундаментальная и клиническая медицина)
Aim. To study reproductive health of women with and without eating disorders.Materials and Methods. We designed an original questionnaire, surveyed and analyzed the medical records of 200 women of reproductive age.Results. All the study participants suffered from eating disorders. Out of 200 patients, 46 (23%), 120 (63%), and 34 (17%) had emotional, restrictive, and external eating disorders, respectively. Women with normal body mass index (BMI) or overweight were more likely to have an avoidant/restrictive food intake disorder while emotional and external types prevailed among obese patients. Fibrocystic breast changes, uterine fibroids, polycystic ovary syndrome, infertility, and breast cancer were significantly more common in women with obesity (r = 0.74 for gynecological diseases in total). Pelvic inflammatory disease was more frequently diagnosed in women with emotional eating disorders while fibrocystic breast changes, uterine fibroids, and polycystic ovary syndrome were more prevalent in those with restrictive food intake disorder. Breast cancer prevailed in women with external eating disorders.Conclusion. Women of reproductive age are frequently diagnosed with different types of eating disorders. Obese women are more likely to have reproductive system disease. Each of eating disorders correlate with different gynecological diseases.